Nematic-isotropic transition in a weakly diluted lattice model: Monte Carlo study - Ilnytskyi, Ja.M. (Condensed Matter Physics, 1999)
We consider a weakly diluted lattice model of elongated particles undergoing a ﬁrst order nematic-isotropic transition in a pure bulk case. The lattice of 20³ sites with a 5% dilution is studied by Monte Carlo simulation and by applying the Ferrenberg-Swendsen histogram technique. The shift of the transition temperature and the decrease of the latent heat and the order parameter due to dilution are calculated. The heat capacity and the susceptibility peaks are essentially suppressed as compared to a pure case. The comparison to the experiments on liquid crystals conﬁned in silica aerogels and porous glasses is done.